Pengaruh Komposisi Pelepah Sawit Terhadap Sifat Dan Morfologi Wood Plastic Composite - Fauzi, Iwan; Bahruddin, Bahruddin; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The availability of palm frond has a potential to use for decrease utilization of woods directly. One application is the wood plastic composite (WPC). Research on the WPC is still growing which aimsto continue to get better quality of product. The objective of this research was to determine the effect of palm frond composition to properties and the morphology of wood plastic composite(WPC). The Composition of palm frond measured at - 40 +80 as the filler and the polypropylene as the matrix is 30:70 which mix with additive 2% and Maleic Anhydride Polypropylene (MAPP) 5%. Palm frond prepared using oxalic acid, potassium hydroxide, sodium hydroxide and hydrogen peroxide at a temperature of 120oC with 15 minutes immersion time. Filler mixing process, matrix, and the additive use Labo Plastomill internal mixer at a temperature of 170oC and the rotor speed at 80 rpm. Tests include cellulose test while the mechanical properties testing are tensile strength and flexural strength, and physical properties include density, water absorption and thickness swelling. Morphology test used the electron microscopy scanning with amagnification of 100 and 500 times. The results showed that the type of preparation has a relatively significant influence. Best WPC material is used oxalic acid mixture at a temperature of 120oC with19,214 MPa tensile strength, flexural strength of 43 639 MPa, density 0974 gr / cm3, 0.32% water absorption and thickness swelling 1.42%.Keyword: filler, palm frond, wood plastic composite